Digital image correlation - Wahono, Natalinus Albion (2012)
In the process of finding similarities between one images and other image, template matching algorithms which give good precision result has been researched largely. Various template matching algorithms have been researched and available to be used for the digital image correlation processing and DIC (digital image processing) is an advance process in this area. Here, high performance software is developed which can be used to find displacement between surfaces before and after deformation as one application of DIC.